1986
DOI: 10.1111/j.1365-2125.1986.tb05213.x
|View full text |Cite
|
Sign up to set email alerts
|

The haemodynamic and myocardial effects of dopexamine: a new beta 2‐ adrenoceptor and dopaminergic agonist.

Abstract: 1 Dopexamine increases inotropic state and rate of relaxation independent of changes in heart rate. 2 Dopexamine has a chronotropic effect and results in a decrease in systemic vascular resistance. 3 Dopexamine has a spectrum of action that should be useful in patients with severe heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(4 citation statements)
references
References 19 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…For dopamine and dobutamine this appears to be dose related whereas for dopexamine this reaches a plateau at the low dose level. This agrees with previous experimental work which showed that a mild increase in contractility is achieved with dopexamine together with reduction in afterload (Jaski et al, 1986).…”
Section: Discussionsupporting
confidence: 93%
“…For dopamine and dobutamine this appears to be dose related whereas for dopexamine this reaches a plateau at the low dose level. This agrees with previous experimental work which showed that a mild increase in contractility is achieved with dopexamine together with reduction in afterload (Jaski et al, 1986).…”
Section: Discussionsupporting
confidence: 93%
“…An afterload-reducing agent and renal vasodilator with positive inotropic activity, dopexamine hydrochloride improves cardiac function in patients with heart failure (Dawson et al, 1985;Svensson et al, 1986) and suspected coronary artery disease (Jaski et al, 1986). Plasma levels typically obtained in man (0.02-0.61M; internal reports and Jaski et al, 1986) and in anaesthetized dogs (0.08-0.4tiM; Dr D Hall, personal communication) with therapeutic-dose infusions of dopexamine hydrochloride, would on the basis of these in vitro studies, be within the concentration range able to produce Uptake, block, and it is suggested that the inotropic response is partially mediated by Uptake, blockade and hence potentiation of endogenous noradrenaline.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma levels typically obtained in man (0.02-0.61M; internal reports and Jaski et al, 1986) and in anaesthetized dogs (0.08-0.4tiM; Dr D Hall, personal communication) with therapeutic-dose infusions of dopexamine hydrochloride, would on the basis of these in vitro studies, be within the concentration range able to produce Uptake, block, and it is suggested that the inotropic response is partially mediated by Uptake, blockade and hence potentiation of endogenous noradrenaline. The ability to block neuronal uptake of noradrenaline is shared by two other clinically used positive inotropic catecholamines, dopamine (Iversen, 1971) and dobutamine, although these are at least ten fold weaker than dopexamine hydrochloride.…”
Section: Discussionmentioning
confidence: 99%
“…It is a potent 032-adrenoceptor agonist but has no a-adrenoceptor activity. The compound also inhibits neuronal re-uptake of catecholamines (Svenson et al, 1988), so it may affect agonist receptor interactions in this fashion (Jaski et al, 1986). Furthermore it has no appreciable P I-receptor activity (Brown et al, 1985a;Heitz et al, 1983) and evidence suggests it has potent inotropic properties probably via myocardial P2-adrenoceptors (Miller et al, 1981).…”
Section: Introductionmentioning
confidence: 99%